The Effect of Using Meta Cognitive Strategies on the Development of Reading Comprehension in English language on the Second Grade of Secondary students in Jeddah City - Almutayri, Fatimah Miteib; Alghazu, Khitam Mohammed (Journal of Educational and Psychological Sciences, 2019)
The current study aimed to find out the effect of using meta cognitive strategies on the development of reading comprehension in English language on the Second Grade of Secondary students in Jeddah city. The researcher used a quasi-experimental approach with two groups (control group and experimental groups). The sample, which included (58) female students from the second grade of secondary students on Jeddah city, was convenience sample. The researcher prepared three tools for studying as the following: • A list of reading comprehension skills in English language. • A test of a reading comprehension in English language. • A guide book for teacher and students to use the meta cognitive skills. The researcher used appropriate statistical methods as the Means, standard deviations, and one way ANOVA and MANCOVA, the following results have been reached: 1- There are statistical significant differences at the level of ≤ 0.05 between the average post-test scores of the experimental group and the average post-test scores of control group in all reading comprehension levels of English language for experimental group after controlling pretest for experimental group. 2-There are no statistical significant differences at the level of ≤ 0.05 between the average post-test scores of the experimental group and the average post-test scores of control group in literal comprehension level of English language after controlling pre-test for experimental group. 3- There are statistical significant differences at the level of ≤ 0.05 between the average post-test scores of the experimental group and the average post-test scores of control group in interpretative comprehension level of English language after controlling pre-test for experimental group. 4- There are statistical significant differences at the level of ≤ 0.05 between the average post-test scores of the experimental group and the average post-test scores of control group in critical comprehension level of English language after controlling pretest for experimental group. The study has recommended to develop the English curriculum in order to apply the implementation of meta cognitive strategies, as well as, to train the teachers of English language before and during the service on using the meta cognitive strategies. The study has suggested to study the effectiveness of other strategies for " meta cognition " in the development of reading comprehension. Also, it has suggested to study the effectiveness of the " meta cognition " strategies for the development of language skills in different stages of learning.